Private Bank Money vs Central Bank Money: A Historical Lesson for CBDC Introduction - Anna Grodecka-Messi (Lund University, School of Economics and Management, Department of Economics, 2019)
In this paper, a unique event is studied: the opening of Bank of Canada in 1935, the central bank note issuance monopoly and its impact on the note issuing chartered banks. Between 1935-1950, Canadian chartered banks had to gradually withdraw their notes from circulation. In a difference-in-differences analysis, I show that chartered banks constrained by new issuance limits experienced higher volatility of return-on-equity in the short run and lower Z-scores and return-on-assets in the longer horizon, suggesting that note issuance was an important source of revenue for private banks and allowed them to smooth the profits. The effect on lending is either non-significant or ambiguous. This study of central bank cash implementation can offer lessons for the current debates on a new form of central bank money - central bank digital currencies - and their potential impacts on commercial banks.
Keywords: E42; E50; G21; G28; N22; 330; Banknote Monopoly; Banknote Issuance; Cash; Central Bank Digital Currencies; Double Liability; Canadian banks; Financial Stability; Bank of Canada